Comparative responses to a physical activity program in older adults - Carlos X. Torres-Ramos; Rachel E. Salyer; Isaura M. Castillo-Hernández; Ellen M. Evans (Cogent Gerontology)
The aim of this pilot study was to examine whether sex/gender influences the effects of a 10-week physical activity (PA) intervention on engagement, PA behaviors, muscle capacity, and lower extremity physical function (LEPF) in older adults (OAs). Physically inactive OAs (71.3 ± 4.3 years old; n = 28, 64% female) completed a PA program that included: a twice-weekly supervised exercise class, Facebook engagement, and an unsupervised walking prescription. PA (accelerometer, questionnaires, and logs), muscle capacity (leg strength and power), LEPF [6-minute walk (6 MW), 8-foot up and go (UPGO), chair stands (CHAIR), transfer task (TRANSFER)], program engagement, and Facebook participation (attendance logs) were assessed. A two-way [Gender (G) x Time (T)] ANOVA and independent samples t-test were utilized to compare differences and significance of change. Females engaged with Facebook 2.3 times more than males (p = 0.01). Muscle capacity improved similarly in both sexes, although males exhibited greater overall leg strength and power (G p < 0.05; T p < 0.05). Improvements in LEPF were observed in 6 MW, UPGO, and TRANSFER (T p < 0.05; GxT p > 0.05), with males having higher functional capacity overall in 6 MW, UPGO, and CHAIR (G p < 0.05). Further implementation research is needed to develop effective and sustainable multicomponent PA programs for OAs, considering social factors that may differ.